Effect of an educational program about mentorship competencies on nurse mentors' performance: a quasi-experimental study - Heba Moussa Hagrass; Sanaa Abd El-Azeem Ibrahim; Rasha Ibrahim El-Sayed Anany; Heba E. El-Gazar (BMC, 2023)
Abstract Background Mentorship is a vital part of the nursing profession to improve role transition, job satisfaction, and job retention while facilitating socialization, emotional well-being, and the acquisition of new skills. Aim The present study aimed to evaluate the effect of an educational program about mentorship competencies on nurse mentors' performance at Port Said Healthcare Authority hospitals. Methods A quasi-experimental study design (pre-test and post-test one group) was used to conduct the study at seven Healthcare Authority hospitals in Port Said Governorate, Egypt. The study subjects were consisted of a purposive sample of 30 nurse mentors and 60 intern nursing students. Data were collected using three tools consisted of the Mentor Knowledge Questionnaire, Mentor Competencies Instrument (MCI), and Nurse Mentor Performance Assessment. Data analysis was performed using SPSS version 20, Student's t-test was used to measure differences between the pretest and post-test, and Qualitative categorical variables were compared using the chi-square test. A significant level value was considered when the p-value ≤ 0.05, and Cohen's d was used to measure the effect size. Results the post-test scores of mentorship competencies and performance after implementation of the educational program significantly improved in the studied nurse mentors 56.1 ± 13.2, 60.5 ± 4.9 compared with pre-test scores with 37.1 ± 4.1, 49.7 ± 6.9 (P < 0.001). As determined by Cohen's d test, the effect size of an educational program is quite large on the nurse mentors' performance. Conclusion The educational program about mentorship competencies was significantly improve mentorship performance of the studied nurse mentors. The study recommended dissemination and generalization of the new and innovative mentorship program to the different stages of nursing education to foster the continued growth and development of nurse mentors and nurse students. Also, recommended developing a valid mentor assessment instrument consisting of and specific to the Egyptian context to assess the Egyptian mentorship model. Trial Registration Number (TRN) The study protocol was approved by the Research Ethics Committee of the Faculty of Nursing, Port Said University (code number: NUR 13/2/2022) [10].